Heterologous Expression of Two Malate Transporters From an Oleaginous Fungus Mucor circinelloides Improved the Lipid Accumulation in Mucor lusitanicus - Xiuwen Wang (Frontiers Media S.A., 2021)
The fungus, Mucor lusitanicus, is of great interest for microbial lipids, because of its ability to accumulate intracellular lipid using various carbon sources. The biosynthesis of fatty acid requires the reducing power NADPH, and acetyl-CoA, which is produced by the cleavage of citrate in cytosol. In this study, we employed different strategies to increase lipid accumulation in the low lipid-producing fungi via metabolic engineering technology. Hence, we constructed the engineered strain of M. lusitanicus CBS 277.49 by using malate transporter (mt) and 2-oxoglutarate: malate antiporter (sodit) from M. circinelloides WJ11. In comparison with the control strain, the lipid content of the overexpressed strains of mt and sodit genes were increased by 24.6 and 33.8%, respectively. These results showed that mt and sodit can affect the distribution of malate in mitochondria and cytosol, provide the substrates for the synthesis of citrate in the mitochondria, and accelerate the transfer of citrate from mitochondria to cytosol, which could play a significant regulatory role in fatty acid synthesis leading to lipids over accumulation.